Pattern recognition and features selection for speech emotion recognition model using deep learning - Jermsittiparsert K.; Abdurrahman A.; Siriattakul P.; Sundeeva L.A.; Hashim W.; Rahim R.; Maseleno A. (Springer, 2023)
Deep learning; Feature extraction; Learning systems; Speech; Feature selection methods; Features selection; Input sources; Maximum accuracies; Recognition models; Recognizing models; Speech emotion recognition; Speech sounds; Speech recognition